The Causes of Family Orphanhood (Archives of Criminology, 1982)
The study contains the results of an empirical research carried out in Poland devoted to the macro- and microsocial conditions of family orphanhood. In the first stage (1978), 97% of the population of all children’s homes, inhabited at the time of the study by 24,000 persons, were examined, and in the second stage (1980), 2.1% of this population were examined (520 persons, which made the sample representative of the country).                The notion of family orphanhood was introduced in the study to describe the situation of children who are under care of State institutions due to the lack of care in their own families. The notion of social orphanhood is thus limited - in this formulation - to the situation when the State, in spite of negligence of basic parental duties by the parents, has not yet taken over the care of the child.                The extent of social orphanhood in Poland is rated at approximately 10% of the population of children and young people aged 0-17. The extent of family orphanhood is rated at approximately 5 promile in the age group 4-18. The growth of family orphanhood shows the triple increase of the phenomenon during the last 20 years.                At the time of the study, 58% of family orphans were in State; children's homes. From the point of view of the research tasks, this group of children and young persons was considered the most representative, as the principles of placing children under other forms of care (that is, for instance, foster homes, family children's homes, centres for school education and special educational institutions for socially maladjusted children and young people) are based on particular criteria of selection.                Below a summary of the results of the study is presented.The greatest intensity of family orphanhood and crime can be found in the western and northern regions of Poland. As revealed by the statistical analysis, the intensity of these phenomena in various parts of the country is significantly correlated. Their joint source are the by-products of social changes.In the social conditions promoting the phenomenon of anomy, the group patterns of deviant behavior may reach broader social circles; the tendency to perceive that behavior as contradictory to the norms diminishes then. This tendency concerns criminal behavior to a much greater extent than the behavior from which the family orphanhood results. Thus the growth of social orphanhood measured indirectly (for instance, by the rate of care and protection cases in courts), seems to be more diagnostic as a ratio of increase of pathogenic social phenomena than as an index of reported crime.The growth of pathogenic social phenomena can be studied indirectly by means of a structure analysis of attributes of the population selected in a particular way. The structure of particular attributes of the population of institutions for children and juveniles varies significantly according to the intensity of the pathogenic social  phenomena in different parts of the country. In the voivodships where this intensity is greater, a higher percentage of children under psychiatric care or those whose parents have been deprived of their parental rights, is to be found significantly more frequently; the distributions of frequency in the separate age groups are random in the examined population. In the voivodships where the ratio of pathogenic social phenomena is lower, the most numerous age group is that of 13-15, which means that - more often than in the remaining voivodships - the important reason for sending children to institutions are their educational problems connected with puberty, and not a generally worse situation of the families which would cause sending children to institutions regardless of their age.On the microsocial scale, the main cause of family orphanhood is the disorganization of the family related to the individual and social characteristics of the parents. Taking into account the level of disorders in the social behavior and that of disturbances in emotional relations between the members of the family, 4 categories of families were distinguished in the population examined. The majority are the familiesdisturbed both in their social functions and in emotional relations; there were as many as 78.2% of them among 5200 families. The families which, however undisturbed, were educationally inefficient for other objective reasons (financial problems, housing problems, illness, disability, death of one parent were 7.1% of the cases. There were also 8.5% of the families with only emotional relations disturbed, and 6.3% of those with only social behavior disturbed. Thus the majority, that is, as much as 84.5% of the children were brought up in criminogenic environment.75.3% of fathers and 55% of mothers were regularly drinking excessively; alcoholism was found in 55.6% of fathers and 19.6% of mothers; 66.6% of the mothers’ friends who lived together with the family were heavy drinkers. The high percentage of drinking  mothers in those families should be noted.                Lack of a permanent employment was found among 27.6% of fathers and 41% of mothers. Due to their alcoholism and poor professional training, a considerable part of the children's guardians found it difficult to obtain and keep a job.                Until the time of the study, 15% of fathers and 6% of mothers had already been imprisioned; no reliable information was gathered as to their previous criminal records.                Professional prostitution was found among 12% of mothers, while sexual promiscuity among as many as 40%.                The instability of emotional bonds is a striking feature of the families examined. Only 1/3 of the parents are married. In 53% of the cases, the parents admittedly live together, but one of them is temporarily absent due to imprisonment or stay in a mental hospital, which are the most frequent reasons.                73% of the families live in very difficult financial conditions, 61% have serious housing problems.                A very poor state of health (serious chronic diseases) was found in 18% of fathers and 23% of mothers.Health and physical development of children and youths in children’s homes are distinctly worse than the average in the country. Their height in 49,3% of the cases does not reach the age norm, the respective percentage in the case of weight being 42%. A half of the children had suffered from serious diseases, as shown by 48.6% of the cases of hospitalization. In as much as 17% of the children the past or present diseases are connected with damages of the central nervous system or with functional changes which reflect on their mental functions (cerebral concussion, epilepsy, acute neuroses). 17% of the ailments and diseases are immediately related to grave neglect (untreated advanced form of tuberculosis, effects of accidents). Congenital defects are found in 5% of cases.In the group of family orphans, the types of mental deficiency and personality disorders which impede the normal social functions can be found more frequently than in the entire population of children and young people.                Only 56% of the children came within the limits of the normal intelligence level. The symptoms of nervousness - more or less intense - were observed among as many as 90% of them. There were only 13% of the children without any disturbances of behavior (that is, inhibition, increased kinetic restlessness, timidity, emotional sensitivity, aggressiveness etc.).                Developmental deficiencies were found in as many as 84% of the children; the most frequent were those in the sphere of the development of visual (34.5%) and auditory (22.3%) functions, the least frequent were the disturbances of speech (13.8%).Deviant behavior is more frequent among the concerned population than in the entire population of children and youths in respective age groups. The following three types of behavior proving the threat of demoralization were found: behavior connected with school maladjustment, with environmental maladjustment against the background of defective emotional relations (excluding the one based on emotional disorders of the passive type, like inhibition, timidity, etc.) and delinquent behavior or that pointing to disturbed socialization. The most frequent are the types of behavior revealing school, maladjustment (41.4%), those revealing distrubances of emotional relations (28%), and the least frequent are types of behavior of deliquent character or pointing to disturbed socialization.                It is worthy of notice that the intensity of behavior of the first and third types markedly decreases in the children’s homes, while in the case: of the second type, that is of behavior revealing disturbances of the emotional sphere, the decrease is much less visible. In the conditions of the children’s home the emotional compensation, which is an important problem, is difficult to solve.